Effect of desmopressin on hemochromocytometric and clotting parameters in healthy blood donor dogs - Giudice, Elisabetta; Giannetto, Claudia; Casella, Stefania; Arcuri, Giuseppe; Piccione, Giuseppe (Journal of Applied Biomedicine, 2009)
Six clinically healthy blood donor dogs were used to evaluate the effect of desmopressin (DDAVP) on haemochromocytometric and clotting parameters,. They received subcutaneously a physiological solution (placebo) and DDAVP (1microg/kg) with a two-weeks wash-out period between treatments. Blood samples were collected immediately before the injection, after 30 minutes, then after 1, 2, 3, 4, 5 and 6 hours. Two-way repeated measure analysis of variance (ANOVA) showed no significant effect of DDAVP vs placebo, except for white blood cell (WBC) count, and in particular on neutrophils. In conclusion, DDAVP administration in healthy donor dogs does not induce modification in blood cell count and clotting parameters, except of WBC.
Keywords: cytologické techniky; Blood Coagulation Tests; Blood Cells; psi; Blood Donors; vyšetření krevní srážlivosti; Statistics as Topic; Animal Experimentation; desmopresin; dárci krve; Cytological Techniques; krevní buňky; experimenty na zvířatech; Deamino Arginine Vasopressin; Dogs; statistika jako téma; Veterinary Medicine; veterinární lékařství